COCCINITE, ΗgI2, FROM A BURNING DUMP OF THE ALMAZNAYA COAL MINE (EASTERN DONBAS): THE FIRST FIND IN RUSSIA - A.V. Kasatkin; I.V. Pekov; O.V. Trofimov; A.A. Agakhanov; M.D. Milshina; S.N. Britvin (Минералогия)
An extremely rare mercury iodide coccinite, ΗgI2, was found in a burning dump of the Almaznaya coal mine (near the settlement of Gukovo, Rostov oblast, Russia). It forms bright red tabular and short-prismatic crystals with adamantine luster up to 0.5 mm in size on a crust of native sulfur, which fills the fractures in the burnt rock. This is the first find of coccinite in the Russian Federation. The reflectance values and quantitative chemical analysis of coccinite are published for the first time. The chemical composition of the mineral is as follows (wt. %, mean of five analyses, electron microprobe): Hg 45.15, Cl 0.11, Br 0.65, I 53.91, total 99.82. The empirical formula calculated based on sum of three atoms is Hg1.02I1.93Br0.04Cl0.01. The strongest reflections of the powder X-ray diffraction diagram are [d,Å(I)(hkl)]: 6.220(29)(002), 4.122(82) (101), 3.575(100)(102), 3.008(37)(103), 2.767(35)(112), 2.189(98)(114, 200). The parameters of the tetragonal unit cell calculated from the powder data are as follows: a = 4.3744(2), c = 12.4301(7) Å, V = 237.86(2) Å3. Coccinite crystallized from hot gases after the combustion of coal-bearing rocks in the inner part of the dump.